Qiyās Mustawā Waʿy al-Muʿallimīn bi-Istikhdām al-Wasāʾiṭ al-Mutaʿaddidah fī Tadrīs al-Mahārāt al-Lughawiyyah li-Talāmīdh al-Marḥalah al-Ibtidāʾiyyah fī Niyāmī, al-Nījar: Dirāsah min Wajhat Naẓar al-Muʿallimīn - Nourroudine Abdoulaye Mamoudou (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The integration of multimedia into language instruction has become increasingly important; however, its successful implementation depends on teachers’ awareness, curriculum readiness, and the availability of supporting facilities. This study aimed to assess teachers’ awareness of multimedia use in teaching Arabic language skills at primary schools in Niamey, Niger, while examining the availability of multimedia resources and the suitability of the curriculum for technology integration. A descriptive quantitative design was employed using a structured questionnaire administered to 40 Arabic language teachers. The collected data were analyzed using SPSS with descriptive statistical techniques. The findings revealed a high level of teachers’ awareness of multimedia use (M = 4.07) and a very high level of curriculum suitability (M = 4.51). However, the availability of multimedia facilities and technological infrastructure was only moderate (M = 3.20). These findings indicate that infrastructure remains the primary challenge despite positive teacher perceptions and curriculum readiness. The study contributes empirical evidence from Niger and provides practical recommendations for improving infrastructure and strengthening teacher professional development to support effective multimedia-based Arabic language instruction.